Millennial Generation Preferences for Subsidy House Selection in Kendal Regency - Naufal, Muhammad Fadhiil Hardian; Sarwadi, Ahmad (Universitas Negeri Yogyakarta, 2025)
Housing is a fundamental human need providing shelter, security, and comfort. Preferences in housing vary among consumers, particularly across different generations. This study aims to identify millennial preferences in subsidized housing and the factors influencing these preferences in Kendal Regency. Quantitative research methodology was employed, utilizing exploratory secondary data collection. Variables included design, housing type, location, geography, and costs. Data collection involved both secondary and primary sources, with questionnaires distributed to 120 millennial beneficiaries of subsidized housing loans in Kendal Regency. Data analysis encompassed univariate and bivariate analysis. Chi Square test showing significant associations were found between income, occupation, age, and geographic location with housing preferences, highlighting the importance of economic and demographic factors in shaping housing decisions. Education, however, did not show a significant impact on these preferences. These findings underscore the need for targeted policies and marketing strategies to meet the diverse housing preferences of millennials in subsidized housing contexts.